Changing Cities in the Perspective of Religious Tourism – A Case of Allahabad. (2016) - Chadha, Harsimran; Onkar, Preeti
Abstract: Urban planning is a tool, which enables in managing changes within a spatial approach. It helps in conducting planning activities where the economic, environmental, and social goals are taken care of holistically. Planning process involves studying past trends, learning from past and present, and then preparing a proposal for future. This process mostly assesses the trend of growth and plans for development. A trend follows change in a defined rate. An indefinite or unexpected change spoils the planning process, by breaking the trend of growth. City is known for its resources, geography, population, social-culture structure, economy etc. Whenever there is an unexpected change in any of these parameters, the city undergoes remarkable changes. Disaster also brings hasty changes in all these, which is indeed a challenge to urban planning and design. The fast modernization and adoption of western culture leads to significant changes in socio-cultural and economic spheres. City also changes, when rapid movement of people and resources occur. Tourism industry in this decade brought many changes is Indian cities. It diversifies social and cultural identity of the city and generates tremendous opportunity for economic development. Therefore cities having tourism potential are facing urban planning problems. Exploring these issues and reasons behind it will be helpful to minimize its impact. Tourism cities have tremendous potential of research in this direction. The need of the decade for urban planners and designers is to be prepared for the changes in a tourist city.